Porous media representation of louvers in building simulations for natural ventilation. Issue 4 (4th July 2019) - Ooi, Chinchun; Chiu, Pao-Hsiung; Raghavan, Venugopalan; Wan, Stephen; Poh, Hee Joo
Abstract : Many buildings have louvers on their facades or windows, as they reduce penetration of wind-driven rain, indoor glare and irradiance from the sun and external noise. However, these louvers typically have millimetre-scale blade thicknesses and slat pitch, while spanning metres across the building in a full simulation domain of several kilometres. Consequently, computational fluid dynamic models require vastly increased cell counts to explicitly resolve these fine features for accuracy, which is computationally expensive. An alternative is to utilize a porous media model based on the Darcy–Forchheimer law to reduce the cell count. We present a method to determine parameters for a porous media representation of louvers, and quantify the associated deviation in velocity and pressure in a simplified building simulation. We show errors in the air velocities after passage through the porous media zone ranges from <10% in the simplest models to 38% in more complex cases.